2013
DOI: 10.1016/j.jtcvs.2013.05.043
|View full text |Cite
|
Sign up to set email alerts
|

Process improvement in cardiac surgery: Development and implementation of a reoperation for bleeding checklist

Abstract: A substantial reduction in reoperation for bleeding cases followed implementation of a formalized hemostasis checklist. Our findings underscore the important influence of memory aids that focus attention on surgical techniques to improve patient outcomes in a complex, operative work environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 28 publications
0
38
0
1
Order By: Relevance
“…The number of operations per year came from a workforce survey of 1211 surgeons performed by the Society of Thoracic Surgeons . We predicted a 2.0% to 1.5% rate of decreased operative complications for BRC and RFB, respectively, as a result of the educational intervention based on the incidence of these complications . In the OIA base case, we modeled 3 in 10 participants implementing learning to prevent a BRC or RFB.…”
Section: Methodsmentioning
confidence: 99%
“…The number of operations per year came from a workforce survey of 1211 surgeons performed by the Society of Thoracic Surgeons . We predicted a 2.0% to 1.5% rate of decreased operative complications for BRC and RFB, respectively, as a result of the educational intervention based on the incidence of these complications . In the OIA base case, we modeled 3 in 10 participants implementing learning to prevent a BRC or RFB.…”
Section: Methodsmentioning
confidence: 99%
“…Foremost among these are investigations of blood product use [12, 13]. We studied the effect of transfusion and reoperation for bleeding on outcomes [12, 13] and developed and implemented a reoperation for bleeding checklist that resulted in a reduction in reoperations for bleeding [14]. We evaluated the frequency of laboratory testing in patients undergoing cardiac operations and proposed strategies to reduce phlebotomy volumes for preventing hospital-acquired anemia [15].…”
Section: Commentmentioning
confidence: 99%
“…There was a 1.8-fold increased risk of composite outcome (adjusted rate 3.33%, 95% CI 3.09-3.58%) in patients managed by low-performance anaesthesiologists compared with high-performance anaesthesiologists (adjusted rate 1.82%, 95% CI 1.58-2.10%) [49 && ]. Furthermore, a study by Loor et al demonstrated that implementing an intra-operative checklist in collaboration between anaesthesiologist and surgeon minimizes postoperative bleeding due to technical reasons, and leads to significantly less need for re-exploration [50]. Making use of this information, CABG outcomes may further improve with team (surgeons and anaesthesiologists) initiatives, such as Flawless Operative Cardiovascular Unified Systems (FOCUS), to decrease mortality [51].…”
Section: Refinements In Anaesthesiamentioning
confidence: 99%